Continuous flow doebner–miller reaction and isolation using continuous stirred tank reactors - Yadav, Maruti B.; Kulkarni, Sourabh; Joshi, Ramesh A.; Kulkarni, Amol A. (Organic Process Research & Development, 2016)
Continuous flow Doebner–Miller synthesis of different quinaldines from respective anilines is demonstrated using sulfuric acid as a homogeneous catalyst. The extent of reaction was monitored for various parameters, namely, temperature, residence time, mole ratio of sulfuric acid to substrate, mole ratio of crotonaldehyde to substrate, and so forth. Continuous stirred reactors in series were used as a preferred configuration for this rection that generates byproduct in the form of sticky solid material. The approach has been extended for six different anilines, and the results are compared with batch reactions. Continuous stirred reactors in series with distributed dosing of crotonaldehyde facilitated a continuous flow reaction with lower byproduct formation, increased yields, and continuous workup and is a scalable approach.